Overweight, obesity, and screen-time viewing among Chinese school-aged children: National prevalence estimates from the 2016 Physical Activity and Fitness in China-The Youth Study - Yujun Cai; Xihe Zhu; Xueping Wu (Elsevier, 2017)
Purpose: This study presents the most recent estimates of prevalence of overweight, obesity, and screen-time viewing among Chinese school-aged children. Demographic differences in these estimates between sexes and resident locales were also examined. Methods: Cross-sectional analyses of 116,615 Chinese school children 9 to 17 years of age who participated in the 2016 Physical Activity and Fitness in China-The Youth Study project. Outcomes were the prevalence of children's overweight (85th ≤ body mass index (BMI) < 95th percentile) and obesity (BMI ≥95th percentile) (defined by the Working Group on Obesity in China) and not meeting screen-time viewing recommendations ("not meeting" was defined as more than 2 h per day of viewing activities after school). Analyses were conducted on the whole sample and by school grade cohorts (primary, junior middle, and junior high schools), sex, and residence locales (urban, rural). Results: Overall, 14.4% (95% confidence interval (CI): 13.8%-15.0%) of children and adolescents were overweight, 11.9% (95%CI: 11.0%-13.0%) were obese, and 36.8% (95%CI: 34.7%-38.9%) did not meet screen-time viewing recommendations. Across the 3-grade cohorts, boys were more likely to be obese than girls, and primary and junior middle school children living in urban areas were more likely to be obese than those living in rural areas. Primary and junior middle school boys were less likely to meet screen-time recommendations than girls, and junior high school children living in urban areas were less likely to meet screen-time recommendations than school children of the same grades living in rural areas. Conclusion: In 2016, the prevalence of obesity among Chinese school children was about 12%, and about 37% of them did not meet screen-time viewing recommendations. The prevalence of obesity and sedentary behavior was generally higher among boys than among girls, and it was higher for children living in urban areas than for those living in rural areas.